Review on Frequency Neurofeedback on Autism Spectrum Disorder: Overview, Efficacy and Research Direction - Ryan, Alexander (Journal of Psychophysiology Practice and Research, 2025)
Frequency neurofeedback (FNF) is a biofeedback method that targets frequencies between 1 and 50 Hz. The efficacy of FNF with autism has been labeled ‘probably efficacious’ in literature reviews in the last decade, despite new research pointing towards a higher standard. The aim of this review was to analyze key features of these studies, with a goal of determining the efficacy standard of FNF on autism and establishing a research direction. Electronic databases and literature reviews were used to collect a total of ten randomized and/or matched controlled trials. FNF reaches a Level 4 efficacy standard, with an impact on a broad range of factors including core autistic traits, social communication, emotional regulation, cognitive flexibility, executive function, behaviors of concern, attention, metabolic or thermal activity, and EEG e.g. decreased absolute power, mu rhythm, coherence and hyperconnectivity. Current evidence generalizes to male children, up to 18 years, with a low-average or higher intellectual functioning, with autism as the only diagnosis. A meta-analysis suggests a large superior effect when compared to wait list controls. Current research does not meet the higher efficacy standards outlined by Arns et al. (2020). Small samples plague most studies, and the maintenance of improvements post-training are yet to be assessed adequately. Eight recommendations are made.
Keywords: Neurofeedback; neurofeedback training; autism; ASD; literature review; efficacy